Effect of Different Growing Media on Growth Performance of Liberica Coffee Rootstock - Ismail, Ahmad Arif; Pa'ee, Furzani; Abd Rani, Muhammad Naim Fadzli; Mohd Nor, Azlan Azizi; Radhi, Mohd Zafrul Arif; Ismail , Khairol (Journal of Sustainable Natural Resources, 2023)
Liberica coffee is a hardy perennial crop grown by smallholders as a monocrop or intercrop with coconut or other fruit trees. The current propagation method of Liberica coffee clones is based on grafting, which requires 7-8 months for rootstock to mature and another 7-8 months for planting. The current production manual suggests using a 1:1 ratio of soil to sand to produce matured Liberica coffee rootstock. Studies have shown that using a combination of planting media, such as rice husk charcoal and compost, can result in higher plant height, number of leaves, internodes, and leaf area. A combination of leaf manure, silt, straw, peat moss, and soil performed better than 100% soil due to better nutrients, water, and anchorage provision. Consequently, a study to assess the impacts of growing media on MKL 1 polyhybrid as rootstock was carried out. The experimental design used was Randomized Complete Block Design (RCBD) with 4 replications. Treatment consist of T1 = soil + sand (1:1), T2 = soil + cocopeat (1:1), T3 = soil + peat moss + sand + cocopeat (1:1:1:1), T4 = soil + peat moss + cocopeat (2:1:1), T5 = soil + peat moss (3:1), T6 = soil + chicken manure (3:1) and T7 =  soil + CIRP (10:1). Parameters evaluated in this study include plant height, leaves number, stem girth, SPAD, fresh root weight and dried root weight. The findings indicate that the treatments had a significant impact on girth, SPAD, and root fresh weight and these three parameters share significant positive association with one another. Girth performed best under T4 although fresh root weight and SPAD performed noticeably better under T3. Current recommended protocol for media performed significantly lower compared to other media. This study offers a new outlook on how to improve current protocol on Liberica coffee rootstock preparations.